1993
DOI: 10.2134/jpa1993.0350
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Late Spring Soil Nitrate Concentrations and Corn Yields in New York

Abstract: Proper N management is important to optimizing profit and minimizing N loss. The efficiency of N use may be improved in humid regions with a reliable soil test to guide fertilizer N recommendations. Recently, a presidedress nitrate soil test (PSNT) has shown promise as a means of quantifying the size of the potential mineralizable organic N pool in soil. This study was conducted to determine if the PSNT could be used for corn (Zea mays L.) production to identify N responsive and non‐responsive sites, predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
2
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 8 publications
7
36
2
3
Order By: Relevance
“…In similar conditions, but for lower yield expectations (yield goal of 10 t grain·ha -1 ), Villar et al [25] found that a PSNT 0-30 cm level between 94 and 142 kg N·ha -1 (21 to 32 mg NO 3 -N·kg -1 ) was required. These values are also in concordance with the PSNT 0-30 cm levels found by other researchers [10,16,27]. The results from site P-2 suggest that, after alfalfa, corn does not need supplemental N fertilizer applications in this region, regardless of the soil nitrate levels found at sidedressing.…”
Section: The Pre-sidedress Soil Nitrate Test (Psnt 0-30 CM ) As a N Fsupporting
confidence: 91%
“…In similar conditions, but for lower yield expectations (yield goal of 10 t grain·ha -1 ), Villar et al [25] found that a PSNT 0-30 cm level between 94 and 142 kg N·ha -1 (21 to 32 mg NO 3 -N·kg -1 ) was required. These values are also in concordance with the PSNT 0-30 cm levels found by other researchers [10,16,27]. The results from site P-2 suggest that, after alfalfa, corn does not need supplemental N fertilizer applications in this region, regardless of the soil nitrate levels found at sidedressing.…”
Section: The Pre-sidedress Soil Nitrate Test (Psnt 0-30 CM ) As a N Fsupporting
confidence: 91%
“…Although the goal in amenity turfgrass is not to maximize the yield, similar critical values between turf-type and forage-type grass yields suggest that the maximum growth response of perennial cool-season grasses, whether for forage or turfgrass use in our climate, will be reached at soil NO 3 -N concentrations approaching 10 to 15 mg kg . The crops that have been studied include silage corn (Magdoff et al, 1990;Fox et al, 1989;Meisinger et al, 1992;Klausner et al, 1993;Sims et al, 1995), field pumpkin (Cucurbita pepo L.) (Morris et al, 2000), sweet corn [Zea mays subsp. saccharata (Sturtev.)…”
Section: Clippings Dry Matter Yieldsmentioning
confidence: 99%
“…Soil nitrate concentration at this time reflects carry-over of residual nitrate from the previous growing season, much of the additional soil mineral N resulting from spring applied manure (Zebarth and Paul 1997) and as much as 60% of the apparent growing season soil N mineralization (Zebarth et al 2001). The PSNT can be used to predict the sidedress rate of mineral fertilizer (Zebarth et al 2001) or liquid manure (Ball-Coelho et al 2005); however, the PSNT is generally more effective in identifying fields that will be responsive to sidedress N application than in predicting the optimal fertilizer N rate to apply at sidedress (Klausner et al 1993). In some cases, PSNTbased recommendations are adjusted for heavily manured fields (Jemison and Lytle 1996) or fields that have been under wet spring conditions (Scharf 2001).…”
Section: Soil-based Diagnostic Testsmentioning
confidence: 99%